Engineered Cell‐Membrane‐Coated Nanoparticles Directly Present Tumor Antigens to Promote Anticancer Immunity. Issue 30 (15th June 2020) - Jiang, Yao; Krishnan, Nishta; Zhou, Jiarong; Chekuri, Sanam; Wei, Xiaoli; Kroll, Ashley V.; Yu, Chun Lai; Duan, Yaou; Gao, Weiwei; Fang, Ronnie H.; Zhang, Liangfang
Abstract: The recent success of immunotherapies has highlighted the power of leveraging the immune system in the fight against cancer. In order for most immune‐based therapies to succeed, T cell subsets with the correct tumor‐targeting specificities must be mobilized. When such specificities are lacking, providing the immune system with tumor antigen material for processing and presentation is a common strategy for stimulating antigen‐specific T cell populations. While straightforward in principle, experience has shown that manipulation of the antigen presentation process can be incredibly complex, necessitating sophisticated strategies that are difficult to translate. Herein, the design of a biomimetic nanoparticle platform is reported that can be used to directly stimulate T cells without the need for professional antigen‐presenting cells. The nanoparticles are fabricated using a cell membrane coating derived from cancer cells engineered to express a co‐stimulatory marker. Combined with the peptide epitopes naturally presented on the membrane surface, the final formulation contains the necessary signals to promote tumor antigen‐specific immune responses, priming T cells that can be used to control tumor growth. The reported approach represents an emerging strategy that can be used to develop multiantigenic, personalized cancer immunotherapies. Abstract : Cancer cells are genetically engineered to express a co‐stimulatory marker that enables them to directly present their own antigens under an immunostimulatory context. Cell‐membrane‐coated nanoparticles sourced from these modified cells elicit antitumor immunity in vivo while bypassing the need for traditional cell‐mediated antigen presentation. This approach may ultimately enable the facile design of personalized artificial antigen presentation platforms.